High loading-dose of dupilumab resulted in rapid disease control in pediatric patients with atopic dermatitis - Wang, Ao; Zhou, Yuan; Luo, Yang; Gao, Yingxia; Chen, Jingsi; Li, Wei; Luo, Xiaoyan; Yao, Xu (Frontiers in Immunology, 2023)
Background The real-world experience of dupilumab in Chinese is limited, and the initial loading dose has not yet been deeply explored in patients aged <6 years. Objective To explore the efficacy and safety of dupilumab in Chinese patients with moderate-to-severe atopic dermatitis and investigate the effect of higher loading dose for disease control in patients aged <6 years. Methods A total of 155 patients were divided into three groups according to age: <6 years, 6-11 years, and >11 years. Among patients aged <6 years, 37 patients received a high loading dose of 300 mg for body weight <15kg or 600 mg for body weight ≥15kg, and another 37 patients received a standard loading dose of 200 mg for body weight <15kg or 300 mg for body weight ≥15kg. Multiple physicians and patient-reported outcome measures were evaluated at baseline and 2, 4, 6, 8, 12, and 16 weeks after dupilumab treatment. Results The proportion of patients showing an improvement of ≥75% in the Eczema Area and Severity Index was 68.0% (17/25), 76.9% (10/13), and 62.5% (25/40) in the aged <6, 6-11, and >11 years groups, respectively, at week 16. After increasing the loading dose, 69.6% (16/23) of patients aged <6 years achieved 4-point improvement in Numerical Rating Scale at week 2, compared with 23.5% (8/34) of patients receiving standard loading dose (P < 0.001). Obesity (odds ratio=0.12, 95% confidence interval: 0.02-0.70) was predictive of a poor response to dupilumab treatment, while female (odds ratio=3.94, 95% confidence interval: 1.26-12.31) predicted good response at week 16. The change of serum C-C motif ligand 17(CCL17/TARC) could reflect the response to dupilumab (r = 0.53, P = 0.002 in EASI) among patients aged <18 years. No major adverse events were reported during the treatment. Conclusions Dupilumab was effective and well-tolerated in Chinese patients with atopic dermatitis. The increased loading dose helped achieve rapid pruritus control in patients aged <6 years.